2002
DOI: 10.1097/00007632-200208150-00021
|View full text |Cite
|
Sign up to set email alerts
|

Surgery for Solitary Metastases of the Spine

Abstract: Patients with solitary sites of spine involvement from solid tumors represent a biologically favorable subgroup with potential for long-term survival. In this group, complete surgical excision before irradiation should be considered to increase the prospects of long-term palliation and possible cure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
107
0
18

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 228 publications
(130 citation statements)
references
References 27 publications
5
107
0
18
Order By: Relevance
“…The previously described techniques were modified [7,32,37,58,59], prognostic surgical scores [56,57,60,61] were established considering the underlying tumor biology, the number/presence of extraspinal metastases and an estimation of life expectancy. With the results of these scores and the tremendous advance in spine surgery technique the indication from primary spinal tumors is now extended to selected cases of solitary spinal metastases with biologically favorable tumor entities [1,54,62,70]. Thanks to advances in tumor screening and diagnostics, the number of patients who may benefit from this extensive surgical treatment continues to increase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The previously described techniques were modified [7,32,37,58,59], prognostic surgical scores [56,57,60,61] were established considering the underlying tumor biology, the number/presence of extraspinal metastases and an estimation of life expectancy. With the results of these scores and the tremendous advance in spine surgery technique the indication from primary spinal tumors is now extended to selected cases of solitary spinal metastases with biologically favorable tumor entities [1,54,62,70]. Thanks to advances in tumor screening and diagnostics, the number of patients who may benefit from this extensive surgical treatment continues to increase.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical treatment had been prevented by the thoracolumbar spine's close proximity to the surrounding neurovascular structures, i.e., the aorta, caval vein, myelon and nerve roots. Therefore, an intralesional corpectomy by piecemeal resection was considered as the only feasible surgery [12,22,23,26,33,54,64,68] followed by anterior-posterior stabilization of the resulting segmental spinal defect. However, the overwhelming majority of these intralesional resection patients have shown a poor oncological outcome [17,44,64].…”
Section: Introductionmentioning
confidence: 99%
“…Interpretation of these striking differences included less violation of the tumor border, minimized tumor cell contamination and decreased tumor tissue derived blood loss. Application of these principles on solitary spinal metastatic disease have reinforced the concept of aggressive surgical treatment in selected patients, with biologically favorable cancers, who have the potential of long-term survival [3,28,39]. Despite conclusive evidence for significantly improved survival is missing to date, Sundaresan et al have shown that among 80 patients with solitary spinal metastases who underwent gross resection of tumor by various techniques, the rate of locoregional recurrences for the entire series was 32%, whereas only 17% of the patients who underwent en bloc resection experienced local recurrence [28].…”
Section: Discussionmentioning
confidence: 99%
“…A more aggressive approach has been taken by the oncologists and surgeons managing patients with spine metastases, and especially for solitary metastases has shown a favorable outcome [6]. These are due to improvement in the pain, maintenance of function, decrease in the recurrence and potential for improvement in the neurological status [7].…”
Section: Discussionmentioning
confidence: 99%